2020
DOI: 10.1002/lary.29221
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and Systemic Inflammation Synergistically Impact Survival in Oral Cavity Cancer

Abstract: Objectives Sarcopenia and systemic inflammation can affect survival of advanced‐stage oral squamous cell carcinoma (OSCC) patients; however, their reciprocal associations with survival outcomes are yet to be investigated. Study Design Retrospective review at a tertiary cancer center. Methods Patients with stage III‐IVB OSCC that underwent surgery and (chemo)radiotherapy at our institution between 2010 and 2015 were reviewed. Skeletal muscle index (SMI) was assessed using computed tomography scans at the C3 ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 43 publications
1
35
2
Order By: Relevance
“…We screened the titles and abstracts of these studies and identified 83 potentially eligible studies. The full-text versions of these 83 studies were then inspected according to the exclusion criteria, and 18 studies involving 3,233 patients were determined to be eligible for inclusion in this study [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] (Table 1). In these 18 studies, seven investigated patients treated with surgery [17, 20, 25-27, 31, 32] and 10 investigated patients treated with RT [15, 16, 18, 19, 21-24, 29, 30].…”
Section: Literature Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…We screened the titles and abstracts of these studies and identified 83 potentially eligible studies. The full-text versions of these 83 studies were then inspected according to the exclusion criteria, and 18 studies involving 3,233 patients were determined to be eligible for inclusion in this study [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] (Table 1). In these 18 studies, seven investigated patients treated with surgery [17, 20, 25-27, 31, 32] and 10 investigated patients treated with RT [15, 16, 18, 19, 21-24, 29, 30].…”
Section: Literature Search Results and Study Characteristicsmentioning
confidence: 99%
“…[31] used the psoas muscle mass index, and the study by Choi et al [21] used the skeletal muscle area of the neck. The remaining 16 studies used skeletal muscle mass index (SMI), with seven [15,18,23,25,[27][28][29] and nine [16,17,19,20,22,24,26,30,32] studies measuring the muscle area at the L3 and C3 spine levels, respectively. Eight studies [16, 18, 19, 22-24, 29, 30] in the RT group and six studies [17,20,[25][26][27]31] in the surgery group reported stage distribution between stage I, II and stage III, IV disease.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…We obtained data regarding the neutrophil-lymphocyte ratio (NLR) as a systemic inflammatory marker from medical records. NLR was categorized as high or low using a cut-off of 3 [ 38 , 39 ]. The bowel V45, which indicates the bowel volume (mL) receiving a radiation dose of ≥45 Gy [ 9 ], was obtained from the patient’s radiotherapy plan.…”
Section: Methodsmentioning
confidence: 99%
“…Although sarcopenia, frailty status, and systemic inflammation are relatively well established as negative predictors of clinical outcomes in patients with HNC undergoing surgery [ 18 , 19 , 20 , 21 , 34 , 35 ], the value of these factors to predict patients with OSCC undergoing adjuvant CRT is unclear. The present study analyzed 175 patients with OSCC, among which 64% ( n = 112) had sarcopenia undergoing adjuvant CRT.…”
Section: Discussionmentioning
confidence: 99%